Influence of Homogenization Conditions of Buffalo Milk on the Recovery of Milk Constituents and Yield of Mozzarella Cheese - Jana, A.H.; Modha, Hiral (Journal of Buffalo Science, 2017)
Mozzarella cheese making involves losses of milk constituents, especially during plasticizing stage of cheese curd. Buffalo milk is considered more suitable than cow milk for Mozzarella cheese making, especially in terms of colour, yield and stretch property of resultant product. Homogenization of milk reduces the losses of milk constituents, increases its whiteness and is expected to render superior flavor to cheese. The fat globule size for buffalo milk is larger and the cheese tends to be firmer and chewy as compared to cow milk counterpart. Homogenization of buffalo milk is of significance in this regard since it can improve the color, recovery of milk constituents culminating in higher cheese yield, a mellower product with lower tendency to oil-off during baking applications. Since the conditions of homogenization affects the recovery of milk constituents, it was decided to study temperature and pressure of homogenization on such aspect including cheese yield. Homogenization of standardized buffalo milk at 55 or 65oC and 4.90 MPa (P2) pressure is found beneficial with regard to recovery of milk fat, while use of lower pressure i.e. 2.45 MPa (P1) at above temperatures is found beneficial for protein and TS recoveries. P2 pressure is more beneficial than P1 pressure in improving the fat recovery in buffalo milk Mozzarella cheese. There is an improvement in the yield of Mozzarella cheese with an increase in homogenization pressure. The yield of Mozzarella cheese prepared using buffalo milk homogenized at P2 and P1 pressure (at 65oC) was 17.00% and 16.10% respectively. The recoveries of milk fat, protein and TS and per cent yield for control cheese was 83.68%, 84.10%, 56.74% and 14.53% respectively.